2012
DOI: 10.1177/2047487312451252
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing antihypertensive medication compliance in Taiwan: a nationwide population-based study

Abstract: Several patient- and institution-related factors may influence medication compliance. Therefore, for optimal outcomes, patients' awareness of the need for compliance with antihypertensive therapy must be enhanced, and effective intervention strategies should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
5
26
2
1
Order By: Relevance
“…We also found that, in the upstream level, place of residence, education level, and health education were related to compliance behaviors of hypertensive patients. In this study, participants who lived in rural areas were less likely to comply with medication than those who lived in urban areas, which is consistent with a population-based study in Taiwan [ 50 ]. Generally, rural population had relatively low levels of income, education, and health service accessibility and utilization [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…We also found that, in the upstream level, place of residence, education level, and health education were related to compliance behaviors of hypertensive patients. In this study, participants who lived in rural areas were less likely to comply with medication than those who lived in urban areas, which is consistent with a population-based study in Taiwan [ 50 ]. Generally, rural population had relatively low levels of income, education, and health service accessibility and utilization [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies that show hypertensive patients have poor adherence to treatment [17-19], which may be the primary cause of uncontrolled hypertension [16]. On the other hand, there may be multiple reasons for nonadherence to medications such as poor access to healthcare, cost of medicine, etc.…”
Section: Discussionsupporting
confidence: 91%
“…However, patients in our study had relatively lower adherence and persistence rate compared with existing studies (adjusted MPR; FDC vs. FC, at 6 month: 66.55% vs. 63.86%; at 1 year: 52.58% vs. 46.73%). These variations can be explained by the heterogeneity of patient population , variations of treatment employed and culture differences .…”
Section: Discussionmentioning
confidence: 99%